**y=4**

**x=1**

i dont know how to do this

please explain

Thanks

Tutors, sign in to answer this question.

Hi Angelica;

5x+y=9 and 10x-7y=-18

The coefficients of x are 5 and 10. To apply the practice of elimination, we want only one coefficient.

Let's take the first equation...

5x+y=9

Let's multiply both sides by 2...

2(5x+y)=(9)(2)

10x+2y=18

Let's subtract this from the second equation...

10x-7y=-18

-(10x+2y=18)

10x-10x=0

-7y-2y=-9y

-18-18=-36

0-9y=-36

The x is eliminated.

-9y=-36

Let's divide both sides by -9...

(-9y)/-9=-36/-9

A negative number divided by a negative number has a positive result...

Let's plug this into either equation to establish the value of x. I randomly select the second...

10x-7y=-18

10x-[(7)(4)]=-18

10x-28=-18

Let's add 28 to both sides...

28+10x-28=-18+28

10x=10

Let's divide both sides by 10...

(10x)/10=10/10

Let's plug both values into the first equation to verify results...

5x+y=9

[(5)(1)]+4=9

5+4=9

9=9

First, align each equation:

5x + y = 9

10x - 7y = -18

Second, you must eliminate the x's or the y's. Let's choose the y's. Therefore, multiply the top equation by 7 (both sides of the equal sign)

7 * (5x + y) = 9 * 7

35x + 7y = 63

10x - 7y = -18 Now, add the two equations. This gives a result of

45x = 45 Divide both sides by 45 and x = 1.

Substitute x = 1 into either original equation 5 (1) + y = 9; 5 + y = 9. Subtract 5 from both sides of equal sign. y = 4.

Answer x = 1 and y = 4

To answer this by elimination do the following:

5x+y=9

10x-7y=-18

Multiply top equation by -2

-2(5x+y)=9(-2)

10x-7y=-18

Now multiply out the -2 in the first equation:

-10x-2y=-18

10x-7y=-18

Now vertically add the comonents:

-9y=-36 <---- (-10x + 10x = 0, -2y + -7y = -9y, and -18 + -18 = -36)

Divide each side by -9

-9y/-9 = -36/-9

y=4

Not just substitute 4 back into an equation and solve for x:

5(x) + 4 = 9

5(x) = 5

x = 1

Now double check your work (use the opposite equation to make sure)

10(1)-7(4)=-18

10-28=-18

-18=-18

Viola! All done. I hope you enjoyed this step-by-step answer!

5x+y=9 .... multiply both sides by 2 ... 10x+2y=18

10x-7y = -18

subtract the second equation from the first, giving 9y = 36 [2y-(-7y)= 9y; 18- (-18) = 36]

y=4

substitute y = 4 into either equation, solve for x

I'll use the second ... 10x-(7)(4) = -18 ... 10x-28 = -18 ... 10x = 10 (adding 28 to both sides) ... x= 1

Check for correctness using the first equation 5*1+4 = 9? yes, it does!

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.